2017
DOI: 10.1136/annrheumdis-2016-210459
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of the biosimilar ABP 501 compared with adalimumab in patients with moderate to severe rheumatoid arthritis: a randomised, double-blind, phase III equivalence study

Abstract: ObjectivesABP 501 is a Food and Drug Administration-approved biosimilar to adalimumab; structural, functional and pharmacokinetic evaluations have shown that the two are highly similar. We report results from a phase III study comparing efficacy, safety and immunogenicity between ABP 501 and adalimumab.MethodsIn this randomised, double-blind, active comparator-controlled, 26-week equivalence study, patients with moderate to severe active rheumatoid arthritis (RA) despite methotrexate were randomised (1:1) to A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
105
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(117 citation statements)
references
References 11 publications
7
105
0
1
Order By: Relevance
“…Data from the preclinical analytical and functional studies, along with the results of the clinical trials, supported FDA approval of infliximab-dyyb with extrapolation to all other diseases for which reference infliximab had already been approved, but which were no longer protected by exclusivity. Similar data on the adalimumab biosimilars BI 695501 (adalimumab-adbm) and ABP 501 (adalimumab-atto), for the etanercept biosimilar GP2015 (etanercept-szzs), and for the infliximab biosimilars SB2 (infliximab-abda) and infliximab-qbtx (PF-06438179/ GP1111) (5) resulted in extrapolation to all nonexclusive indications for which the respective reference products had been approved (29,(34)(35)(36)(37).…”
Section: Extrapolation Of Indications Switching and Substitution Anmentioning
confidence: 67%
“…Data from the preclinical analytical and functional studies, along with the results of the clinical trials, supported FDA approval of infliximab-dyyb with extrapolation to all other diseases for which reference infliximab had already been approved, but which were no longer protected by exclusivity. Similar data on the adalimumab biosimilars BI 695501 (adalimumab-adbm) and ABP 501 (adalimumab-atto), for the etanercept biosimilar GP2015 (etanercept-szzs), and for the infliximab biosimilars SB2 (infliximab-abda) and infliximab-qbtx (PF-06438179/ GP1111) (5) resulted in extrapolation to all nonexclusive indications for which the respective reference products had been approved (29,(34)(35)(36)(37).…”
Section: Extrapolation Of Indications Switching and Substitution Anmentioning
confidence: 67%
“…For example, the transition studies evaluating the infliximab biosimilar CT‐P13 for RA (Program Evaluating the Autoimmune Disease Investigational Drug cT‐p13 in RA Patients) or ankylosing spondylitis (Program Evaluating the Autoimmune Disease Investigational Drug cT‐p13 in AS Patients) and those for the etanercept biosimilar SB4 were open‐label, single‐arm extension studies . The ADA biosimilar ABP 501 has a similar ongoing single‐arm, open‐label extension study to evaluate efficacy and safety during transition from ADA to the biosimilar . In other studies, patients are rerandomized after a blinded treatment phase to transition to the biosimilar from the reference product, such as the study with the infliximab biosimilar SB2 and the switching study of CT‐P13 in Norway (the NOR‐SWITCH trial) .…”
Section: Discussionmentioning
confidence: 99%
“…A single transition from adalimumab to ABP 501 at week 16 had no impact on the efficacy, safety or immunogenicity results for the remainder of the study. In a separate clinical trial that included patients with moderate‐to‐severe rheumatoid arthritis, ABP 501 and adalimumab have also been shown to be similar with respect to efficacy, safety and immunogenicity . Together these data contribute to the totality‐of‐evidence‐based requirements of showing overall similarity between the proposed biosimilar ABP 501 and its originator adalimumab.…”
Section: Discussionmentioning
confidence: 99%
“…A phase I, single‐dose study of ABP 501 in healthy adults demonstrated similar pharmacokinetics to that of adalimumab . To establish similarity between ABP 501 and adalimumab in clinical efficacy, safety and immunogenicity, two phase III studies were conducted: one in patients with moderate‐to‐severe rheumatoid arthritis (NCT01970475) and the other in patients with moderate‐to‐severe plaque psoriasis (NCT01970488) …”
mentioning
confidence: 83%